Influence of total ozone column (TOC) on the occurrence of tropospheric ozone depletion events (ODEs) in the Antarctic - L. Cao; L. Fan; S. Li; S. Yang (Atmospheric Chemistry and Physics, 2022)
The occurrence of tropospheric ozone depletion events (ODEs) in the Antarctic can be influenced by many factors, such as the total ozone column (TOC). In this study, we analyzed the observational data obtained from ground observation stations and used two numerical models (TUV and KINAL), to discover the relationship between the TOC and the occurrence of ODEs in the Antarctic. A sensitivity analysis was also performed on ozone and major bromine species ( BrO , HOBr and HBr ) to find out key photolysis reactions determining the impact on the occurrence of tropospheric ODEs brought by TOC. From the analysis of the observational data and the numerical results, we suggest that the occurrence frequency of ODEs in the Antarctic is negatively associated with TOC, after screening out the impact on ODEs caused by the solar zenith angle (SZA). This negative impact of TOC on the occurrence of ODEs was suggested to be exerted through altering the solar radiation reaching the ground surface and changing the rates of photolysis reactions. Moreover, major ODE accelerating reactions (i.e., photolysis of tropospheric ozone, H 2 O 2 and HCHO ) and decelerating reactions (i.e., photolysis of BrO and HOBr ), which heavily control the start of ODEs, were also identified. We found that when TOC decreases, the major ODE accelerating reactions significantly speed up. In contrast, the major ODE decelerating reactions are only slightly affected. As a result of the different impacts of TOC on photolysis reactions, the occurrence of ODEs depends negatively on TOC.